Identification and Characterization of Mycoplasma feriruminatoris sp. nov. Strains Isolated from Alpine Ibex: A 4th Species in the Mycoplasma mycoides Cluster Hosted by Non-domesticated Ruminants? - Ambroset, Chloé; Pau-Roblot, Corinne; Game, Yvette; Gaurivaud, Patrice; Tardy, Florence (Frontiers in Microbiology, 2017)
The genus Mycoplasma, a group of free-living, wall-less prokaryotes includes more than 100 species of which dozens are primary pathogens of humans and domesticated animals. Mycoplasma species isolated from wildlife are rarely investigated but could provide a fuller picture of the evolutionary history and diversity of this genus. In 2013 several isolates from wild Caprinae were tentatively assigned to a new species, Mycoplasma (M.) feriruminatoris sp. nov., characterized by an unusually rapid growth in vitro and close genetic proximity to ruminant pathogenic species. We suspected that atypical isolates recently collected from Alpine ibex in France belonged to this new species. The present study was undertaken to verify this hypothesis and to further characterize the French ibex isolates. Phylogenetic analyses were performed to identify the isolates and position them in trees containing several other mycoplasma species pathogenic to domesticated ruminants. Population diversity was characterized by genomic macrorestriction and by examining the capacity of different strains to produce capsular polysaccharides, a feature now known to vary amongst mycoplasma species pathogenic to ruminants. This is the first report of M. feriruminatoris isolation from Alpine ibex in France. Phylogenetic analyses further suggested that M. feriruminatoris might constitute a 4th species in a genetic cluster that so far contains only important ruminant pathogens, the so-called Mycoplasma mycoides cluster. A PCR assay for specific identification is proposed. These French isolates were not clonal, despite being collected in a restricted region of the Alps, which signifies a considerable diversity of the new species. Strains were able to concomitantly produce two types of capsular polysaccharides, β-(1→6)-galactan and β-(1→6)-glucan, with variation in their respective ratio, a feature never before described in mycoplasmas.